The quality of medical services in primary healthcare centres in selected communes of the Lubelskie Voivodeship, as assessed by patients – preliminary reports - Przybylska, Daria; Przybylski, Piotr; Drop, Bartłomiej; Czarnocki, Krzysztof; Przybylski, Wojciech; Drop, Katarzyna; Quinton, Magdalena (Polish Journal of Public Health, 2016)
Introduction. Family medicine has a growing responsibility for the health of an individual, and therefore of society as a whole. Establishing an efficient primary healthcare system requires devising an appropriate management strategy. Surveying the quality assessment of medical services is an important element that influences the future shape of the development and management strategy in communes due to the dynamically changing demographic and economic trends, which are leaving their mark on the functioning of local communities. Aim. Evaluation of quality of medical services in primary healthcare centres in communes of Lubelskie Voivodeship. Material and methods. The anonymous survey was conducted among 60 patients benefitting from the medical services provided in healthcare centres in Niemce (Niemce Commune, Lublin District). An original questionnaire in the form of a poll was used to assess the quality of services provided in primary healthcare centres. Results. The results of surveys carried out among the patients of medical centres providing services in the field of primary healthcare (PHC) demonstrated the high level of satisfaction with the received services among the respondents. However, the accessibility of primary healthcare services outside the business hours of PHC centres and the functioning of prevention and health-education programmes need improvement. Conclusions. Based on the survey results we can conclude that the quality assessment of medical services provided by PHC centres, carried out through the ongoing monitoring of patients’ satisfaction, should be the most important indicator of changes in the management of primary healthcare.